Why Continuous Peripheral Nerve Blocks Fail. Issue 4 (December 2017) - Boezaart, André P.; Zasimovich, Yury
Abstract : Continuous nerve blocks (CNBs), compared with other forms of postoperative analgesia, are less frequently utilized, although postoperative pain control may be improved with their use. Further, it has been demonstrated that the safety and side-effect profiles of opioids and other analgesics are inferior to well-performed CNBs. For CNB success, however, several principles must be adhered to: application of appropriate indications, selection of the correct nerve to block, performance of correct CNB technique, and utilization of correct equipment. Although these are simple concepts, they are often violated and can result in block failure, especially secondary block failure, which occurs once the primary bolus block has worn off. Almost all secondary block failures and medico-legal challenges originate from the violation of ≥1 of these principles. Hilton Law of Anatomy and Fick Law of Diffusion underpin common reasons for CNB failures. In addition, novel developments in our understanding of the macroneuroanatomy and microneuroanatomy may further explain CNB failures.